2018
DOI: 10.1177/0032329218754511
|View full text |Cite
|
Sign up to set email alerts
|

No Money, No Representation: A Case Study of Zeguo Town in China

Abstract: Authoritarian regimes rely on fiscal resources to build patronage networks. And so it is with China. Budget making is usually dominated by government leaders. However, some local governments in recent years have invited ordinary people to review budgets and even to determine parts of budgets. Why would local leaders make themselves accountable to their constituencies in an authoritarian setting? Why would local governments in China tie their own hands? Using detailed description of a township government, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Some studies have identified a connection between certain adoptions of PB and resource availability (e.g. Rios et al, 2017;Ye, 2018), noting that governments were more likely to adopt administrative reforms, including to enhance citizen participation in the budget process, only when there was greater resource availability. Thus, it seems that PB might be a "luxury" to be practiced during good times.…”
Section: Financial Sustainabilitymentioning
confidence: 99%
“…Some studies have identified a connection between certain adoptions of PB and resource availability (e.g. Rios et al, 2017;Ye, 2018), noting that governments were more likely to adopt administrative reforms, including to enhance citizen participation in the budget process, only when there was greater resource availability. Thus, it seems that PB might be a "luxury" to be practiced during good times.…”
Section: Financial Sustainabilitymentioning
confidence: 99%
“…Several factors played a role in facilitating the combination of PB and DP in Zeguo. Fiscal affluence based on land was one important background factor for the introduction of PB through DP (Ye, ). Officials at Wenling City required its townships to examine their budget issues through civic participation in 2008.…”
Section: The Combination Of Pb and Dp In Zeguomentioning
confidence: 99%
“…These formal modifications also encompass the creation, modification, or elimination of rules, governance mechanisms, and techniques in a given policy domain. For instance, scholars might investigate new regulations in a particular area, such as environmental or fiscal policy, or even entirely redesigned institutional arrangements, such as experiments with participatory budgeting (He and Warren 2017;Yan and Xin 2016;Ye 2018).…”
Section: Introductionmentioning
confidence: 99%